Five vs. two initial rescue breaths during infant basic life support: A manikin study using bag-mask-ventilation - Geerts, Anke; Herbelet, Sandrine; Borremans, Gautier; Coppens, Marc; Christiaens-Leysen, Erik; Van de Voorde, Patrick (Frontiers in Pediatrics, 2022)
Background and objectives: Children are more likely to suffer a hypoxic-ischaemic cause for cardiac arrest. Early ventilation may provide an advantage in outcome during paediatric cardiopulmonary resuscitation [CPR]. European Resuscitation Council guidelines recommend five initial rescue breaths [IRB] in infants, stemming from the hypothesis that rescuers might need 5 attempts in order to deliver 2 effective ventilations. This study aimed to verify this hypothesis. Methods: Participants (n= 112, convenience sample) were medical students from the Faculty of Medicine and Health Sciences Ghent University, Belgium. Students were divided into duos and received a 15 minute just-in-time training regarding the full CPR-cycle using BMV. Participants then performed five cycles of 2-person CPR. The IRB were given by 1-person BMV, as opposed to a 2-persons technique during the further CPR-cycle. Correct ventilations for the infant were defined as tidal volumes measured (Laerdal® Q-CPR) between 20 and 60 ml, with n= 94 participants included in the analysis.. The primary outcome consisted of the difference in the % of medical student duoss providing at least 2 effective IRB between 2 and 5 attempts. Results: Off all duos, 55,3% provided correct volumes during their first 2 initial ventilations. An increase up to 72,4% was noticed when allowing 5 ventilations. The proportional difference between 2 and 5 IRB allowed was thus significant (-17,0%, 95% confidence interval [-5.4%; -28.0]). Conclusion: In this manikin study, 5 IRB attempts during infant CPR with BMV increased the success rate in delivering 2 effective ventilations. Besides, students received training emphasizing the need for 5 initial rescue breaths. This study provides evidence supporting European Resuscitation Council guidelines.